2020
DOI: 10.7554/elife.57127
|View full text |Cite
|
Sign up to set email alerts
|

Structure of substrate-bound SMG1-8-9 kinase complex reveals molecular basis for phosphorylation specificity

Abstract: PI3K-related kinases (PIKKs) are large Serine/Threonine (Ser/Thr)-protein kinases central to the regulation of many fundamental cellular processes. PIKK family member SMG1 orchestrates progression of an RNA quality control pathway, termed nonsense-mediated mRNA decay (NMD), by phosphorylating the NMD factor UPF1. Phosphorylation of UPF1 occurs in its unstructured N- and C-terminal regions at Serine/Threonine-Glutamine (SQ) motifs. How SMG1 and other PIKKs specifically recognize SQ motifs has remained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 48 publications
7
63
0
Order By: Relevance
“…LBE, FATC (ATM, ATR) or FRB (DNA-PK), and PRD together assemble a gate through which substrates enter, and extend into the active cleft. The same configuration has been observed within the mTOR complex (Yang et al, 2017) and the SMG1-8-9 complex (Langer et al, 2020;Zhu et al, 2019). For this reason, these enzymes exhibit auto-inhibition forms in the absence of activators.…”
Section: Generality In Activation Mechanismssupporting
confidence: 66%
“…LBE, FATC (ATM, ATR) or FRB (DNA-PK), and PRD together assemble a gate through which substrates enter, and extend into the active cleft. The same configuration has been observed within the mTOR complex (Yang et al, 2017) and the SMG1-8-9 complex (Langer et al, 2020;Zhu et al, 2019). For this reason, these enzymes exhibit auto-inhibition forms in the absence of activators.…”
Section: Generality In Activation Mechanismssupporting
confidence: 66%
“…Therefore, it appears that the PRD regulates the activity and/or activation of PIKKs by modulating access to the active site. Interestingly, it has been recently proposed that the PRD could act as a pseudosubstrate, at least in some PIKKs such as SMG1 and ATM [115]. Accordingly, known phosphorylation sites of mTOR that are coupled to mitogen signaling are located in this region (Thr2446 and Ser2448) [112].…”
Section: Beyond Cell Growth: Tor As a Pikkmentioning
confidence: 99%
“…1c). Moreover, the PIKK regulatory domain (PRD, aa 4009-4039), which is partially disordered in mTOR and SMG1 (Langer et al, 2020;Yang et al, 2017), and closed in ATM, ATR (Jansma et al, 2020;Williams et al, 2020), and in all other DNA-PKcs and DNA-PK complexes, rotated 115° to expose the substrate binding groove. Complex VI also revealed that the activated DNA-PKcs has a potential binding site for inositol hexaphosphate (IP6), which has been shown to activate DNA-PK and NHEJ (Hanakahi et al, 2000).…”
Section: Results Cryoem Structures Of Dna-pkmentioning
confidence: 99%
“…DNA-PKcs is a Ser/Thr kinase of over 4000 residues and a member of the PI3K-related kinase (PIKK) family, which also includes mTOR, ATM, ATR and SMG1 (Baretic and Williams, 2014;Hartley et al, 1995). PIKK kinases play key roles in regulation of responses to nutrient stress (mTOR), misfolded and non-functional RNAs (SMG1), DNA double-strand breaks (DNA-PKcs and ATM) or single-stranded DNA (ATR) (Blackford and Jackson, 2017;Langer et al, 2020;Yang et al, 2017). The kinase activity of DNA-PKcs is modestly stimulated by DNA but becomes fully activated only in the presence of both DNA and Ku70/80, which is known to bind DNA ends (Chan and Lees-Miller, 1996;Hammarsten and Chu, 1998;Mimori et al, 1986;West et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation